2021
DOI: 10.1016/j.automatica.2020.109438
|View full text |Cite
|
Sign up to set email alerts
|

Sparse optimal stochastic control

Abstract: In this paper, we investigate a sparse optimal control of continuous-time stochastic systems. We adopt the dynamic programming approach and analyze the optimal control via the value function. Due to the non-smoothness of the L 0 cost functional, in general, the value function is not differentiable in the domain. Then, we characterize the value function as a viscosity solution to the associated Hamilton-Jacobi-Bellman (HJB) equation. Based on the result, we derive a necessary and sufficient condition for the L … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In [3], it was shown that sparse signals can be more effectively compressed than densely represented signals. Motivated by these various applications, the maximum hands-off control has been proposed for discrete-time systems [4]- [6], uncertain systems [7], stochastic systems [8], [9], and infinite-dimensional systems [10]. A good survey of the maximum hands-off control is given in [11].…”
Section: Introductionmentioning
confidence: 99%
“…In [3], it was shown that sparse signals can be more effectively compressed than densely represented signals. Motivated by these various applications, the maximum hands-off control has been proposed for discrete-time systems [4]- [6], uncertain systems [7], stochastic systems [8], [9], and infinite-dimensional systems [10]. A good survey of the maximum hands-off control is given in [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of results have been established for linear systems, 1-3 nonlinear systems, 4 and stochastic systems. 5 In this study, we focus on a type of sparse control problem called the maximum turn-off control problem, described as follows. Consider a discrete-time linear system with multiple inputs.…”
Section: Introductionmentioning
confidence: 99%
“…If the system has a single input, this problem is exactly the same as the conventional sparse control problem. However, if this is not the case, the problem is somewhat different from the conventional problems, [1][2][3][4][5] in which sparsity is maximized in the elementwise sense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal control theory is a powerful mathematical tool for achieving control objectives while considering, for example, energy efficiency and sparsity of control [1,2]. Optimal control problems arise in a variety of physical, biological, and economic systems, to name a few.…”
Section: Introductionmentioning
confidence: 99%